2022
DOI: 10.2147/opth.s350850
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quality of Vision and Visual Outcomes with Bilateral Implantation of a Non-Diffractive Extended Vision Intraocular Lens with a Target of Slight Myopia in the Non-Dominant Eye

Abstract: Purpose To assess the visual outcomes and quality of vision of patients receiving the AcrySof ® IQ Vivity™ non-diffractive extended vision intraocular lens (NDEV IOL) after uneventful cataract surgery when the non-dominant eye is targeted for slight myopia. Design Single site, prospective, single-arm study. Methods Eligible subjects interested in reducing their dependence on spectacles over a range of working distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 21 publications
(31 reference statements)
6
24
0
Order By: Relevance
“…The use of the minimonovision system in the case of the Vivity lens improves the VA for near vision and increases the degree of independence from ocular correction. In the paper by Newsom T. et al describing the results of binocular Vivity lens implantation with target of slight myopia −0.75 D, 29 of 33 eyes achieved UCNVA binocular 0.2 logMAR or better [ 24 ]. Very similar results were obtained in our patients wih minimovision, whose median binocular UCNVA was 0.2 logMAR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of the minimonovision system in the case of the Vivity lens improves the VA for near vision and increases the degree of independence from ocular correction. In the paper by Newsom T. et al describing the results of binocular Vivity lens implantation with target of slight myopia −0.75 D, 29 of 33 eyes achieved UCNVA binocular 0.2 logMAR or better [ 24 ]. Very similar results were obtained in our patients wih minimovision, whose median binocular UCNVA was 0.2 logMAR.…”
Section: Discussionmentioning
confidence: 99%
“…As you know, the use of a minimovision system in the cases of the Vivity lens improves near vision acuity and increases the degree of independence from spectacle correction. Newsom T. et described a high level of satisfaction and a greater degree of independence from ocular correction with the monovision system than without monovision with implantation of the same lens [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers demonstrated that multifocal IOLs were more prone to visual disturbance than EDOF lenses, but others reported no difference [ 9 , 10 ]. Previously studied EDOF and multifocal IOLs are related to higher rates of visual disturbance compared to monofocal IOLs [ 7 ], however which may be addressed by EDOF lens with monovision correction since IOL effect and monovision offset will produce cumulative effects [ 11 ]. Besides, relative to traditional implantable collamer lens (ICL) without central hole, it is more effective in diminishing major postoperative complication, cataract [ 12 , 13 ], possibly due to the improved aqueous humor (AqH) circulation to the crystalline lens anterior surface [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mini-monovision or micro-monovision has been used to compensate for the relatively small power of extended depth-of-focus IOLS. Newsom and Potvin reported favorable results of −0.75 D monovision in the nondominant eye, in terms of improved near vision, increasing the rate of glasses independence [ 26 ]. In our study, eyes with an sSE lower than -0.50 D had poorer UDVA than other eyes, although there was no significant gain in UNVA compared with eyes that had an sSE between -0.50 and 0.00 D. These data suggest that micro-monovision within -0.50 D would result in a favorable outcome for UDVA and UNVA.…”
Section: Discussionmentioning
confidence: 99%